2015
DOI: 10.1155/2015/928631
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Effects of Transcranial Direct Current Stimulation on Electroencephalography in Children with Autism: A Randomized Crossover Controlled Trial

Abstract: Abnormal synaptic maturation and connectivity are possible etiologies of autism. Previous studies showed significantly less alpha activity in autism than normal children. Therefore, we studied the effects of anodal tDCS on peak alpha frequency (PAF) related to autism treatment evaluation checklist (ATEC). Twenty male children with autism were randomly assigned in a crossover design to receive a single session of both active and sham tDCS stimulation (11 mA) over F3 (left dorsolateral prefrontal cortex). Pre- t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 45 publications
4
92
0
4
Order By: Relevance
“…In a randomized crossover trial in 20 children with ASD, 1 mA anodal tDCS for 20 minutes over the left DLPFC (F3 on a 10–20 montage) increased peak alpha frequency (an EEG measure correlated to cognitive performance) and significantly improved scores on the Autism Treatment Evaluation Checklist (ATEC), with the results showing a positive correlation between the two [80]. In another crossover trial with 20 children showed significant improvements in both the Childhood Autism Rating Scale (CARS) and the ATEC with 20 minutes of left frontal 1 mA anodal tDCS [81]; 2 mA anodal stimulation for 30 minutes over the left DLPFC corresponded to improved syntax acquisition using the Bilingual Aphasia Test in 10 minimally verbal autistic children [82].…”
Section: Tdcs Therapeutic Potentialmentioning
confidence: 99%
“…In a randomized crossover trial in 20 children with ASD, 1 mA anodal tDCS for 20 minutes over the left DLPFC (F3 on a 10–20 montage) increased peak alpha frequency (an EEG measure correlated to cognitive performance) and significantly improved scores on the Autism Treatment Evaluation Checklist (ATEC), with the results showing a positive correlation between the two [80]. In another crossover trial with 20 children showed significant improvements in both the Childhood Autism Rating Scale (CARS) and the ATEC with 20 minutes of left frontal 1 mA anodal tDCS [81]; 2 mA anodal stimulation for 30 minutes over the left DLPFC corresponded to improved syntax acquisition using the Bilingual Aphasia Test in 10 minimally verbal autistic children [82].…”
Section: Tdcs Therapeutic Potentialmentioning
confidence: 99%
“…Prefrontal stimulation was conducted to modulate language and cognitive functions, in which the prefrontal cortex is involved (Schneider and Hopp, 2011). With the same stimulation protocol, but applied in two single sessions of anodal tDCS separated by 1 week, improvements in the social scale and health and behavioral problems scale of the Autism Treatment Evaluation Checklist (but not in the language scale nor the sensory and cognitive awareness scale) and peak alpha EEG power have been described in children with the same age range ( Amatachaya et al, 2015). In a case study (Costanzo et al, 2015), an adolescent girl (14 years old) with autism and comorbid catatonia was treated by 28 daily tDCS sessions (each week from Monday to Friday), in association with the patient's usual medication (20 mg/day of promazine, 400 mg/day of quetiapine, and 600 mg/day of carbolithium).…”
Section: Autismmentioning
confidence: 99%
“…As anodal tDCS is often performed over the left DLPFC, the expected increases in neuronal activity may also influence impaired cognitive functions in a positive way, in particular in patients suffering from Attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (Demirtas-Tatlidede, Vahabzadeh-Hagh, & Pascual-Leone, 2013 ). Indeed in autistic children, a single session of anodal tDCS over the DLPFC was sufficient to increase peak alpha frequency which was significantly associated with symptom improvement (Amatachaya et al, 2015 ).…”
Section: Other Psychiatric Disordersmentioning
confidence: 99%